2017
DOI: 10.1155/2017/8918492
|View full text |Cite
|
Sign up to set email alerts
|

Female Urethral Diverticulum Carcinoma: A Case Report and Literature Review

Abstract: A 48-year-old woman with a history of voiding difficulty visited our hospital. Magnetic resonance imaging revealed a periurethral tumor, which was pathologically diagnosed as an adenocarcinoma via transperineal needle biopsy. Radical cystectomy and urethrectomy were performed, and the urinary tract was reconstructed using an ileal conduit. Pathological examination of a resected specimen confirmed adenocarcinoma of the urethral diverticulum. The patient received adjuvant gemcitabine and cisplatin chemotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…20 Chemotherapy used as neoadjuvant with or without radiation has been shown to be superior to the adjuvant options. 20 Commonly used platinum-based chemotherapy options include the 5-FU/leucovorin/cisplatin, 10 GC, 26,29 MVAC, 26 and paclitaxel/ifosfamide/cisplatin 30 with the only comparison between GC and MVAC showing benefits to similar degrees. 26 GC or MVAC combinations may be used in patients with previous sensitivity to platinum-based therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Chemotherapy used as neoadjuvant with or without radiation has been shown to be superior to the adjuvant options. 20 Commonly used platinum-based chemotherapy options include the 5-FU/leucovorin/cisplatin, 10 GC, 26,29 MVAC, 26 and paclitaxel/ifosfamide/cisplatin 30 with the only comparison between GC and MVAC showing benefits to similar degrees. 26 GC or MVAC combinations may be used in patients with previous sensitivity to platinum-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported benefits in patients treated with platinum-based therapy for urogenital malignancies including the urethral diverticular carcinoma. 10,20,26,[28][29][30] It is important here to note that some cancers may be platinum refractory, and proper identification of treatment options following a failure in platinum-refractory cases should be decided. The role of chemotherapy also varies whether it is used as adjuvant or neoadjuvant with or without radiation.…”
Section: Chemotherapymentioning
confidence: 99%
“…Some cases may involve infection, calculus, and/or malignant tumors. 2 Due to the short urethra and low probability of bladder stone formation, urinary stones in female urethral diverticulum are rare. We report a case of female urethral diverticulum with stones.…”
Section: Introductionmentioning
confidence: 99%